Analisis Pengelolaan Keuangan dan Kekayaan Desa (Studi Kasus di Desa Plesungan Kecamatan Gondangrejo Kabupaten Karanganyar) - Atmaja, Dinar Aji; , Dr.Zulfikar, SE, MSi (2016)
This research aimed to know the village financial management in Plesungan village, subdistrict Gondangrejo, Karanganyar. The method used is descriptive qualitative research and the techniques are research data by depth interviews, observation and documentation. The sample used in this study is the village employees who directly in contact in the village financial statement in Plesungan village, subdistrict Gondangrejo, Karanganyar. The result of the research is that the head of village and the village employees have managed the village financial appropiately to government regulations, it can be proved by there is no improvidence in the village financial. The financial management of Plesungan village shows the transparency from planning, realization, dan responsibility to the people dan the regency and province government. The evidences of receipt note and the cash payment and the village properties are including the SP2D, the receipts of land rental dan market, and the official reports of transferring money to the people. Keywords: the village financial management, the village government, the village financial, the village properties, the village fund allocation, APBDesa